The effect of westward travel across five time zones on sleep and subjective jet-lag ratings in athletes before and during the 2015`s World Rowing Junior Championships - Kölling, S.; Treff, G.; Winkert, K.; Ferrauti, A.; Meyer, T.; Pfeiffer, M.; Kellmann, M. (Journal of Sports Sciences, 2017)
This study examined sleep-wake habits and subjective jet-lag ratings of 55 German junior rowers (n = 30 male, 17.8 ± 0.5 years) before and during the World Rowing Junior Championships 2015 in Rio de Janeiro, Brazil. Athletes answered sleep logs every morning, and Liverpool John Moore`s University Jet-Lag Questionnaires each evening and morning. Following an 11-h westward flight with 5-h time shift, advanced bedtimes (-1 h, P < .001, nyp2 = 0.68), reduced sleep onset latency (P = .002, nyp2 = 0.53) and increased sleep duration (P < .001, nyp2 = 0.60) were reported for the first two nights. Jet-lag symptoms peaked upon arrival but were still present after 6 days. Sleep quality improved (P < .001, nyp2 = 0.31) as well as some scales of the Recovery-Stress Questionnaire for Athletes. Participation was successful as indicated by 11 of 13 top 3 placings. Overall, the initial desynchronisation did not indicate negative impacts on competition performance. As travel fatigue probably had a major effect on perceptual decrements, sleep during travel and time to recover upon arrival should be emphasised. Coaches and practitioners should consider higher sleep propensity in the early evening by scheduling training sessions and meetings until the late afternoon.